Enhancing SQL Learning: Gamified tutorials and flipped classroom synergy - Sandor Kiraly; Tamas Balla; Dora Kiraly; Geoffrey Vaughan (Social Sciences and Humanities Open)
Teaching students to think algorithmically is a common goal for school educators; however, SQL's declarative nature demands a distinct approach to problem-solving. This study explores how a gamified teaching platform, combined with a flipped classroom model, can enhance student performance in introductory SQL courses, offering a more effective method for SQL education. Grounded in Self-Determination Theory, the intervention was designed to support students' psychological needs for competence, autonomy, and relatedness in order to foster intrinsic motivation. A total of 70 high school students aged 17–19 took part in the research. The experimental group engaged with SQL content through lecture videos at home and teacher-facilitated lessons in class, while the control group followed a traditional learning approach. Knowledge assessments were conducted after 4 and 8 weeks of instruction, and the results were analysed using the Wilcoxon Signed Rank Test. Although both groups exhibited comparable knowledge at the study's outset, students in the experimental group achieved significantly higher scores at both the 4-week and 8-week checkpoints. These findings highlight the potential of combining a gamified platform with a flipped classroom model to enhance student outcomes in SQL programming. In addition to improved performance, usage data from the educational platform indicate high levels of voluntary engagement with game-based activities, suggesting increased student motivation. These results underscore the value of integrating interactive, student-centered approaches in early SQL education.